Semiotika SEMIOTIKA ROLAND BARTHES PADA IKLAN MARJAN RAMADHAN 2024 VERSI PUTRI HIJAU - Angesti, Regina Antania; Dwi Puji Prabowo (UNIVERSITAS STEKOM, 2025)
This research analyzes the Marjan advertisement featuring the Putri Hijau version to understand the meanings embedded in its visual elements using Roland Barthes'semiotic approach. The study employs a descriptive qualitative analysis method by dividing the advertisement into several parts through screenshot capture. The analysis is conducted by identifying the denotative and connotative meanings of the advertisement's elements. The findings indicate that this advertisement presents a complex cultural narrative and conveys a specific ideological message to the audience. This study provides insight into how advertisements can serve as an effective persuasive communication medium in conveying cultural and commercial values.